The Effectiveness of Mathematics Learning Using Scientific Approaches Assisted by Powerpoint Media - Nika Fetria Trisnawati; Ruslan Hasyim; Mulyono Mulyono; Arie Anang Setyo; M Fathurrahman Fathurrahman (Department of Mathematics Education University of Muhammadiyah Malang, 2021)
This research is a pre-experimental research with one-group pretest-posttest design that aims to determine the effectiveness of statistical learning through the scientific approach assisted by PowerPoint media. The population of this research is the eighth-grade students even semester of 2017/2018 academic year, which consists of 10 classes. The sampling technique is cluster random sampling. Data about the feasibility of learning and student activities were obtained by using an observation sheet, data about students' responses to learning were obtained using a questionnaire sheet, and to find out the learning outcomes of statistical material a learning achievement test was used. Analysis of the data used is descriptive analysis to describe the implementation of learning, student activities, student responses, and student learning outcomes and inferential analysis to test the research hypothesis. The results showed that: (1) the implementation of learning using the Scientific Approach assisted by Powerpoint media for 5 meetings in the excellent category, (2) student activities in the very effective category, (3) students' responses to learning tended to be positive, (4) learning outcomes students achieve mastery learning 87.88%, an average value of 78.58. Thus from the results of the study it can be concluded that Mathematics Learning with the Scientific Approach assisted by Powerpoint media in Sorong City Junior High School Students on statistical material is effective in improving student learning outcomes.